Upaya Peningkatan Transaksi Penjualan melalui Teknik Promosi Stories untuk Meningkatkan Penjualan pada UMKM XYZ - Yusa, Mochammad; Coastera, Funny Farady; Andreswari, Desi (Jurnal SOLMA, 2023)
Background: Micro, Small, and Medium Enterprises (MSMEs) play a vital role in a country's economic growth. However, the main challenges faced by MSMEs are access to technology and effective marketing. This activity aims to provide training and mentoring to MSME XYZ in Bengkulu to optimize the use of social media, especially Instagram and WhatsApp, as promotional tools. Method: The implementation method of the activity begins with the preparation phase, which includes providing training materials. It is followed by the execution of the activity, which is focused on enhancing the capacity of employees in utilizing social media as a marketing strategy to expand reach and establish relationships with the target market. Evaluation is conducted by monitoring the increase in sales transactions for three months after the implementation of the promotion technique. Result: The results show a significant improvement in sales performance, indicating the success of the marketing strategy through social media story techniques.  Conclusion: The story technique has increased the number of sales transactions, demonstrated by an increase from an average of 6-8 transactions to 11-13 transactions per day.